The Profile of Using Grass Field as a Learning Resource on Ecosystem Materials - Weni Sagala; Ika Chastanti; Dahrul Aman Harahap (Postgraduate, University of Mataram, 2021)
The use of grass fields around the school is one way of learning that is carried out outside the classroom and requires students to be able to reason and understand the material so that high student concentration is needed. The research objective was to determine the use of grass fields as a learning resource on the material for ecosystem components. This study used a descriptive method using a qualitative approach, the data analysis technique was carried out in a descriptive qualitative manner using the Miles damn Huberman model. The results showed that the utilization of grass fields as a learning resource on the material for ecosystem components in Senior High School 1 Silangkitang based on (1) Biology is fun ( 67.70%); (2) facilities and infrastructure (83.80%); (3) Net Field 61.20%; (4) Utilized Field (74.10%); (5) Following (38.70%); (6) Interested (83.80%); (7) Ecosystem Material (41.90%); (8) Learning Outcomes (58%); (9) Finding Facts (41%); (10) Presenting Data (35.40%).